The Influence of Patient-Centered Care Culture on Service Quality in West Javanese Hospitals, Indonesia - Richa Noprianty; Wahyu Wahdana; Winasari Dewi; Vira Yuniar Irawan Yuniar Irawan; Ranti Santika (Fakultas Ilmu-ilmu Kesehatan, 2026)
The involvement of patients and their families is critical for determining the required treatment and for the quality of services provided by health care professionals. Therefore, patient-centered care (PCC) is an important indicator of service quality in health facilities. This study aims to measure the effect of PCC implementation on service quality. This research employed a quantitative, cross-sectional method. The research sample, using proportionate stratified random sampling, comprised 119 professional caregivers (PCG) from the preoperative, intraoperative, and PACU wards at three West Java regional public hospitals. Data was collected through a questionnaire. Data analysis was performed using linear regression and multiple regression. The results showed that the average application of PCC culture was 63.08, and the quality of service was 55.40. PCC implementation was also found to strongly influence service quality (p-value = 0.000; r = 0.860). An increase in PCC culture can increase the service quality score by 0.764. The three hospitals in this study implemented the national hospital accreditation standards in 2022 by applying a PCC culture. Therefore, it is recommended that these hospitals maintain and continuously improve the quality of their PCG services to enhance service quality, patient safety, and prevent adverse events.